Molecular Docking Simulation of Cinchona Alkaloids Derivatives as Anti-cancer Agent - Teni Ernawati (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
One of the triggers of breast cancer is the estrogen hormone. Estrogen α receptors play a role in breast development and growth. Estrogen receptors as molecular targets have been widely reported. Cinchona alkaloids have been known to function as anti-malarial, but recent studies have shown that cinchona alkaloids have other potentially such as anti-cancer, anti-tumor, anti-microbial, anti-HBV, anti-inflammatory, anti-oxidant, anti-obesity. Cinchona alkaloids have been developed as anti-cancer agent. They have comparable reactivity and selectivity of cinchona alkaloids functional to anti-cancer agent. In this study, molecular modeling has been performed on forty-four cinchona alkaloid derivatives. These cinchona alkaloids derived compounds have been evaluated as anti-cancer agent. Herein, we observed molecular interactions between selectivity of cinchona alkaloids with estrogen α receptors (ER-α). The docking simulation showed 3 cinchona alkaloids derivatives (cinchonine 2-chlorobenzoate, cinchonidine benzoate and cinchonine 2-(4-hydroxyphenyl) acetate) have lower free energy Gibs and and low kinetic inhibition compared to tamoxifen (as standard commercial) and there are 14 compounds that have relatively the same activity as tamoxifen from 44 alkaloid chincona derivatives.Keywords: cinchona alkaloids derivatives, quinine, quinidine, cinchonine, cinchonidine, anti-cancer, molecular docking